The use of human neurons for novel drug discovery in dementia research. (2nd April 2016) - Vargas-Caballero, Mariana; Willaime-Morawek, Sandrine; Gomez-Nicola, Diego; Perry, V. Hugh; Bulters, Diederik; Mudher, Amrit
ABSTRACT: Introduction : Although many disease models exist for neurodegenerative disease, the translation of basic research findings to clinic is very limited. Studies using freshly resected human brain tissue, commonly discarded from neurosurgical procedures, should complement on-going work using stem cell-derived human neurons and glia thus increasing the likelihood of success in clinical trials. Areas covered : Herein, the authors discuss key issues in the lack of translation from basic research to clinic. They also review the evidence that human neurons, both freshly resected brain tissue and stem cell-derived neurons, such as induced pluripotent stem cells (iPSCs), can be used for analysis of physiological and molecular mechanisms in health and disease. Furthermore, the authors compare and contrast studies using live human brain tissue and studies using induced human stem cell-derived neuron models. Using an example from the area of neurodegeneration, the authors suggest that replicating elements of research findings from animals and stem cell models in resected human brain tissue would strengthen our understanding of disease mechanisms and the therapeutic strategies and aid translation. Expert opinion : The use of human brain tissue alongside iPSC-derived neural models can validate molecular mechanisms identified in rodent disease models and strengthen their relevance to humans. If drug target engagement and mechanism of cellular action can be validated in human brain tissue, this will increase the success rate in clinical research. The combined use of resected human brain tissue, alongside iPSC-derived neural models, could be considered a standard step in pre-clinical research and help to bridge the gap to clinical trials.